KEBIJAKAN LUAR NEGERI FEMINIS KANADA: Bantuan Canada Fund for Local Initiatives di Indonesia pada Masa Pandemi COVID-19 (2017-2021) - Sekarbumi Drajad Al Anbiya (2022)
Feminism has introduced a new perspective into the International Relations study. Its main argumentation suggests that men and women should have equal opportunities and participation in every sector, including politics. IR Feminist activists believe it will help foreign policymakers recognize and analyze the impact of their policies on all genders, especially women. Gender lens in Feminism has brought a new way of looking through international issues. On June 2017, Canada declared its feminist foreign policy that is Canada's Feminist International Assistance Policy (FIAP). Through FIAP, Canada states that supporting gender equality and empowering women is the best way to establish a more peaceful, inclusive and prosperous world while eradicating poverty. Therefore, to support partnerships, innovations, and advocacy efforts to close the gender gap and increase the chances of success for everyone, FIAP was formed. However, in practice, FIAP cannot yet be stated as a feminist foreign policy. This argument will be proven through descriptive qualitative research methods by processing primary and secondary data obtained through personal interviews and literature reviews. This study will specifically discuss Canada Fund for Local Initiatives (CFLI) assistance to Indonesia to prevent gender-based violence during the COVID-19 pandemic. For this reason, the study will focus on the CFLI's aids to Jakarta Feminist, Indonesian feminist NGO. This study aims to examine the impact of Canadian feminist foreign aid through CFLI in Indonesia during the COVID-19 pandemic. This study will also analyze the performance of FIAP from 2017 to 2021. The results of this research analysis will provide a comparison of FIAP under the concept of feminist foreign policy and foreign aid. Ultimately, FIAP is a feminist foreign aid for international development, while Canadian feminist foreign policy itself is still in the formulation stage.